Karakteristik Fisik, Kimia, dan Struktur Mikro Cookies Terigu-Mocaf dengan Penambahan Bubuk Teh Hitam - Muhammar Akbar Danardi; Siti Tamaroh Cahyono Murti; Yuli Perwita Sari (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2026)
Typically made from wheat flour, cookies can also be prepared using alternative ingredients such as tubers, nuts, or fruit flour. A promising substitute for wheat flour is mocaf flour. Since black tea powder is highly antioxidants, it can be a potential source as the ingredients in the nutritional cookies. This study aimed to determine the concentration of black tea powder addition Broken Orange Pekoe, Broken Orange Pekoe Fanning, and Pekoe Fanning (BOP, BOPF, and PF), and concentrations (2%, 4%, and 6%) specifically affected the physical and chemical properties, antioxidant activity, and structure of cookies. The experimental design of this study used a factorial complete randomized design, with the first factor being the concentration of black tea powder addition and the second factor being the grade of black tea. Cookies were tested for hardness, spread ratio, color (L*, a*, b*), antioxidant activity, and microstructure. The results reveal that hardness increases with the addition of black tea powder concentration at each grade, with the highest being BOP 6% at 3,871.83 g. The increase in tea concentration reduces the spreadability of cookies in all grades. The addition of black tea powder decreases the L*, a*, b* values, making the product darker, less red, and less yellow. Grade PF 6% produced the highest antioxidant activity at 34.24% RSA, as well as a compact microstructure. Thus, cookies made with mocaf substitution and the addition of black tea powder affect the physical and chemical characteristics and enhance the nutritional value, making them functional cookies.